Planetary Geodesy and Remote Sensing 2014
DOI: 10.1201/b17624-11
|View full text |Cite
|
Sign up to set email alerts
|

- Lunar Clinopyroxene Abundance Retrieved from M3 Data Based on Topographic Correction

Abstract: MESSENGER magnetometer data show that Mercury's magnetic field is not only exceptionally weak but also has a unique geometry. The internal field resembles an axial dipole that is offset to the North by 20% of the planetary radius. This implies that the axial quadrupol is particularly strong while the dipole tilt is likely below 0.8• . The close proximity to the sun in combination with the weak internal field results in a very small and highly dynamic Hermean magnetosphere. We review the current understanding o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…A Y 0 2 CMB heat flux pattern combined with internal heating may trigger an unstable odd convective mode which may explain the hemispheric field of Mercury (Cao et al 2014;Wicht and Heyner 2014) as observed by MESSENGER (Anderson et al 2012). While their dynamical scenario is convincing, the justification for a Y 0 2 thermal heterogeneity at the mantle of Mercury is somewhat vague.…”
Section: Future Prospectsmentioning
confidence: 97%
“…A Y 0 2 CMB heat flux pattern combined with internal heating may trigger an unstable odd convective mode which may explain the hemispheric field of Mercury (Cao et al 2014;Wicht and Heyner 2014) as observed by MESSENGER (Anderson et al 2012). While their dynamical scenario is convincing, the justification for a Y 0 2 thermal heterogeneity at the mantle of Mercury is somewhat vague.…”
Section: Future Prospectsmentioning
confidence: 97%
“…This so-called iron snow regime has already been suggested to apply to the present cores of Ganymede (Hauck et al 2006;Christensen 2015;Rückriemen et al 2015) and Mercury (Chen et al 2008;Vilim et al 2010;Wicht and Heyner 2014). It has also been suggested that Mars' core may enter the iron snow regime (Stewart et al 2007) and that the lunar core may have gone through an iron snow episode (Zhang et al 2013;Laneuville et al 2014).…”
Section: Iron Snow Regimementioning
confidence: 99%
“…Other models that predict a strong quadrupole component (e.g., Christensen 2006;Christensen and Wicht 2008) imply a large dipole tilt, which has not been observed. A recent review of the various dynamo models for Mercury can be found in Wicht and Heyner (2014). We only provide a summary here.…”
Section: Mercurymentioning
confidence: 99%
“…The dynamo may be generated exclusively at depth due to stable stratification at the top of the core. For example, the very weak, large-scale, and axisymmetric magnetic field of Mercury (Anderson et al 2011;Oliveira et al 2015) can be explained by a skin effect across a stably stratified layer (Christensen 2006;Christensen and Wicht 2008;Wicht and Heyner 2014). As mentioned above, such a layer was also proposed for the Earth (Pozzo et al 2012;Gubbins and Davies 2013).…”
Section: Introductionmentioning
confidence: 98%